Red cell use in trauma. Issue 2 (April 2020) - Shander, Aryeh; Zacharowski, Kai; Spahn, Donat R.
Abstract : Purpose of review: Red cell transfusions are commonly used in management of hemorrhage in trauma patients. The appropriate indications and criteria for transfusion are still debated. Here, we summarize the recent findings on the use of red cell transfusion in trauma setting. Recent findings: Recent evidence continues to support the long-established link between allogeneic transfusion and worse clinical outcomes, reinstating the importance of more judicious use of allogeneic blood and careful consideration of benefits versus risks when making transfusion decisions. Studies support restrictive transfusion strategies (often based on hemoglobin thresholds of 7–8 g/dl) in most patient populations, although some argue more caution in specific populations (e.g. patients with traumatic brain injury) and more studies are needed to determine if these patients benefit from less restrictive transfusion strategies. It should be remembered that anemia remains an independent risk factor for worse outcomes and red cell transfusion does not constitute a lasting treatment. Anemia should be properly assessed and managed based on the cause and using hematinic medications as indicated. Summary: Although the debate on hemoglobin thresholds for transfusion continues, clinicians should not overlook proper management of the underlying issue (anemia).